PENINGKATAN KETERAMPILAN BERBICARA SISWA MELALUI METODE DISKUSI DALAM PEMBELAJARAN BAHASA INDONESIA KELAS VII SMP MIFTAHUL ULUM BANYUATES SAMPANG - M Tohiruddin; Asri Bariqoh; Heni Adhianata (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Keguruan dan Ilmu Pendidikan PGRI Sampang, Indonesia, 2025)
The speaking skills of secondary school students have declined significantly amid the dominance of passive and non-verbal digital communication. This phenomenon has become a controversial issue because Indonesian language learning is still dominated by lecture methods that do not sufficiently train students' verbal expression. This study highlights a change in the learning approach through the application of the discussion method as a solution to overcome poor speaking skills. The purpose of this study is to improve the speaking skills of seventh-grade students at Miftahul Ulum Banyuates Sampang Junior High School through discussion-based learning. The research used the Classroom Action Research (CAR) method, which was carried out in two cycles, each covering the stages of planning, action, observation, and reflection. Data were obtained through observation, interviews, tests, and documentation, then analyzed using qualitative descriptive techniques (data reduction, presentation, and verification). The results of the study showed a significant improvement in speaking skills, from an average score of 69 in cycle I to 82 in cycle II, with a completion rate of 90%. These findings confirm that the discussion method not only follows the trend of active and collaborative learning but is also an effective solution for fostering students' courage, argumentation skills, and verbal participation in the context of 21st-century Indonesian language learning.